PERAN KARUNIA ROH KUDUS DALAM PELAYANAN ORANG PERCAYA MENURUT 1 KORINTUS DAN APLIKASINYA BAGI ORANG PERCAYA MASA KINI - Paulus Baskoro (STT BIBLIKA JAKARTA, 2021)
The gift of the Holy Spirit are an important part of the life of a believer. The purpose of the gifts of the Holy Spirit is to equip every for service in the body of Chrits. Believers who fulfill their minirty with the gifts of he Holy Spirit will have a tremendous impact on the movement of God;s church and the growth of God;s church in an extraordinary way. However, it is undeniable that there are still many believers who doa not believe in the gift of the Holy Spirit, do not optimize the gifts of the Holy Spirit in their ministry, and some even believe that the gifts of the Holy Spirit are in Bible truth, but do not teach God;s congregation. So that God’s congregation or believers do not have maximum spiritual maturity in Jesus, because there are hidden things that are not known by believers. In order to obtain accurate and accountable data, in this study the authors used the method of writing descriptive literature. The purpose of this writing is Frist, to reveal and straighten out the incorrect view of the gift of the Holy Spirit. Second, describe the true meaning of the gift of the Holy Spirit on 1 Corinthians, Third, explain the application of the gifts of the Holy Spirit in the ministry of believers today.